ViMIC: a database of human disease-related virus mutations, integration sites and cis-effects. Issue Volume 50:Issue D1(2022) (9th September 2021) - Wang, Ying; Tong, Yuantao; Zhang, Zeyu; Zheng, Rongbin; Huang, Danqi; Yang, Jinxuan; Zong, Hui; Tan, Fanglin; Xie, Yujia; Huang, Honglian; Zhang, Xiaoyan
Abstract: Molecular mechanisms of virus-related diseases involve multiple factors, including viral mutation accumulation and integration of a viral genome into the host DNA. With increasing attention being paid to virus-mediated pathogenesis and the development of many useful technologies to identify virus mutations (VMs) and viral integration sites (VISs), much research on these topics is available in PubMed. However, knowledge of VMs and VISs is widely scattered in numerous published papers which lack standardization, integration and curation. To address these challenges, we built a pilot database of human disease-related Vi rus M utations, I ntegration sites and C is-effects (ViMIC), which specializes in three features: virus mutation sites, viral integration sites and target genes. In total, the ViMIC provides information on 31 712 VMs entries, 105 624 VISs, 16 310 viral target genes and 1 110 015 virus sequences of eight viruses in 77 human diseases obtained from the public domain. Furthermore, in ViMIC users are allowed to explore the cis-effects of virus-host interactions by surveying 78 histone modifications, binding of 1358 transcription regulators and chromatin accessibility on these VISs. We believe ViMIC will become a valuable resource for the virus research community. The database is available at http://bmtongji.cn/ViMIC/index.php .